Impact of dengue-preventive behaviors on Aedes immature production in Bang Kachao, Samut Prakan Province, Thailand: a cross-sectional study - Pathavee Waewwab; Sungsit Sungvornyothin; Rutcharin Potiwat; Kamolnetr Okanurak (BMC, 2020)
Abstract Background Controlling sites where mosquitos breed is a key strategy in breaking the cycle of infectious transmission of the dengue virus. Preventive behaviors, such as covering water containers with lids and adding temephos (commercially named Abate sand) in water containers are needed to reduce and control mosquito breeding sites. This study aimed to investigate the impact of dengue-preventive behaviors on Aedes immature production. Methods This cross-sectional study used in-person interviews to record occurrence of dengue-preventive behaviors in Bang Kachao, Samut Prakan Province, Thailand. Larval mosquitos in and around houses were observed and recorded, and covered 208 households. Results It was found that 50% of these households had containers for drinking water and 94% used water containers. Covering water containers with effective lids showed the best success among dengue-preventive behaviors for reducing Aedes immature production. Adding temephos in water containers also was effective. Conclusions Such behaviors substantively affected development of Aedes immatures in and around households.